â€œAnalysis Of The Level Of Welfare Of Farmers in Indonesia in 2009-2013â€ - B01112004, Samsul Bahari (Jurnal Curvanomic, 2016)
Indonesia is known as an agrarian country i.e. a country whose agricultural sector becomes a dominant sector in both employment and contributioan to the Indonesia’ GDP. The farmer’s exchange rate of serves as the indicator used to assess the level of farmers’ welfare. The purpose of this study is to describe the farmer’s exchange rate (FER) and its forming components as well as to map the position of the components. The technique of data analysis used was descriptive. The data used in this research were derived from the Central Bureau of Statistics i.e. the data of Farmers Exchange Rate from 2009 to 2013. The findings showed that during the period from 2009 to 2013 the average FER in Indonesia was 103.27 percent due to the average FER in the province of Lampung which was 118.92 percent. Farmers with the highest income were those in the horticulture sub-sector, in the sub-group of vegetables. Farmers with the lowest income were in the sub sectors of food crops sub-sector, due to the sub-sector of rice. The high index of expenditure paid by farmers was due to the farmers’ expense of household consumptioan in the sub-group of food consumptioan costs. Meanwhile, the lowest farmers’ expenditure was the production costs and the addition of capital goods in the sub-group of land rent, taxes, etc. In many regions in Indonesia there are still farmers who could only meet the necessities of daily life and the provision of agricultural capital goods (break oven point). Keywords: farmer’s exchange rate (FER), farmers’ welfare